2014
DOI: 10.3168/jds.2013-7044
|View full text |Cite
|
Sign up to set email alerts
|

Performance assessment of membrane distillation for skim milk and whey processing

Abstract: Membrane distillation is an emerging membrane process based on evaporation of a volatile solvent. One of its often stated advantages is the low flux sensitivity toward concentration of the processed fluid, in contrast to reverse osmosis. In the present paper, we looked at 2 high-solids applications of the dairy industry: skim milk and whey. Performance was assessed under various hydrodynamic conditions to investigate the feasibility of fouling mitigation by changing the operating parameters and to compare perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(41 citation statements)
references
References 43 publications
(39 reference statements)
4
36
0
1
Order By: Relevance
“…The solute present in the feed can affect the MD flux in several possible ways: by building up the fouling layer at the membrane surface that offers an additional resistance to mass and heat transfer, by lowering the vapor pressure of feed solution, by adsorbing on the membrane surface and by introducing concentration polarization if the convective flux is high. Initial high reduction in flux is consistent with the previous MD studies [50] carried out on whey solution where a rapid flux decline was observed mainly due to adhesion of certain whey components with membrane surface. Time interval ($3 h) over which the major flux decline takes place is different in current study as compared to one mentioned in [50] perhaps due to different type of whey and membrane used.…”
Section: Helical and Wavy Modulessupporting
confidence: 92%
“…The solute present in the feed can affect the MD flux in several possible ways: by building up the fouling layer at the membrane surface that offers an additional resistance to mass and heat transfer, by lowering the vapor pressure of feed solution, by adsorbing on the membrane surface and by introducing concentration polarization if the convective flux is high. Initial high reduction in flux is consistent with the previous MD studies [50] carried out on whey solution where a rapid flux decline was observed mainly due to adhesion of certain whey components with membrane surface. Time interval ($3 h) over which the major flux decline takes place is different in current study as compared to one mentioned in [50] perhaps due to different type of whey and membrane used.…”
Section: Helical and Wavy Modulessupporting
confidence: 92%
“…This leads to an increase in the concentration of dissolved ions close to the membrane interface, reducing the local vapor pressure and thereby reducing flux, in addition to increasing tendency to precipitate [124].…”
Section: Increased Temperature and Concentration Polarizationmentioning
confidence: 99%
“…At concentration factor of above 10, inorganic salts in the feed exceeded their saturation limits, precipitated on the membrane surface, and induced membrane scaling. A scaling layer was formed on the membrane, reduced the active surface for water vapour transport through the membrane [40,41] and partial water vapour pressure on the membrane surface [42,43], thus decreasing water flux. The scaling layer could also promote membrane wetting [44,45].…”
Section: Dcmd Concentration Of Csg Ro Brinementioning
confidence: 99%